Associations between the quality of life of children with chronic diseases, their parents' quality of life and family coping strategies - Lucie Sikorová; Radka Bužgová (University of Ostrava, 2016)
Aim: The survey aimed at determining the associations between the quality of life of children with chronic diseases, the quality of life of their parents and coping strategies used in the family. Design: A cross-sectional study. Methods: The study was performed as quantitative research using a questionnaire survey in chronically ill children (n = 288) aged 2-12 years and their parents. The following instruments were used: Pediatric Quality of Life Inventory, Pediatric Quality of Life Inventory Family Impact Module and Family Crisis Oriented Personal Evaluation Scales. Results: The association between the quality of life of diabetic children and their parents' quality of life, family functioning and the impact of the illness on the family was weak. Children with diabetes had the highest quality of life but the quality of life of their parents was lowest among all disease groups in the study. The lowest overall quality of life of children was noted among those with juvenile idiopathic arthritis. The strongest positive associations between internal coping strategies (i.e. reframing and passive appraisal) and children's and parents' quality of life was observed in the families of children with asthma. Conclusions: The weak association between children's and parents' quality of life and coping strategies pointed to their low effectiveness. The results suggest that relevant interventions should be used that promote selection of new coping strategies.